Legal Protection for Investors against Fraud by Market Manipulation in the Indonesian Capital Market - Rahman, Yogi Muhammad; Lalu Saipudin; AH. Asari Taufiqurrohman; Anik Kunantiyorini; Taufiq (Magister of Law, Faculty of Law, University of Mataram, 2024)
Fraudulent acts through market manipulation in the capital market can lead to investors receiving false information in their investment decisions, resulting in unprotected investor funds and unsustainable capital market industry operations. This article employs a normative legal method. Market price manipulation in the capital market falls under the category of fraud in the capital market as it is done with the intention of self-gain and deception, creating a semblance not based on actual material facts to influence others to buy, sell, or hold securities. Protection for investors can be achieved through two approaches: preventive measures by mandating all issuers to adhere to the principle of full disclosure supervised by the Financial Services Authority, and criminal measures where perpetrators of fraud in the capital market can face sanctions of up to 10 years imprisonment or fines of Rp 15 billion following Article 104 of the Capital Market Law. However, existing regulations are still insufficient in protecting the legal interests of investors from fraudulent activities in the capital market due to several factors including the ineffectiveness of the Capital Market Law, weak law enforcement, lack of legal protection mechanisms for investors who suffer losses due to market manipulation, and sanctions deemed ineffective.